PEMIKIRAN INTEGRATIF TEOLOGI DAN KEWIRAUSAHAAN: MEMBANGUN PARADIGMA KEWIRAUSAHAAN BERBASIS SPIRITUALITAS - Margianto, Aris (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2025)
This study explores the integration of theological values into modern entrepreneurship, particularly in shaping an ethical, inclusive, and sustainable business paradigm. The background lies in the shift of business orientation from merely pursuing financial profit to embracing social responsibility, justice, and environmental sustainability. Theological principles such as stewardship, social justice, and love are considered as moral foundations that guide business decision-making. The research employs a qualitative approach, combining case study and descriptive-analytic methods. Data were collected through literature review and observation of entrepreneurial practices that integrate spiritual dimensions. Analysis was conducted interpretatively to identify patterns and meanings that emerge from theologically grounded business practices. Findings reveal that theology-based entrepreneurship extends the triple bottom line (profit, people, planet) by adding a fourth dimension: spirituality. Entrepreneurs driven by faith tend to uphold integrity, transparency, and social as well as ecological concern. Spiritual values also foster eco-friendly innovation, strengthen customer and employee loyalty, and enhance the social contribution of businesses within communities. This study concludes that the integration of theology and entrepreneurship not only opens new interdisciplinary perspectives for academia but also provides practical alternatives. Theology-based entrepreneurship can serve as a transformative agent that promotes justice, sustainability, and the well-being of all creation.